Perancangan User Experience Aplikasi Adopsi Kucing dengan Metode Design Thinking (Studi Kasus: Pecinta Kucing di Malang) - Yolanda Saputri; Agi Putra Kharisma; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The community's interest in keeping cats has increased, but there are still cases of abandoned cats. Many cat lovers find abandoned cats but can't adopt them, so they want to find adopters. However, they find it difficult to find adopters who want to adopt the cat due to the lack of media as a bridge to disseminate this information. Based on these problems, this research was carried out to design a user experience application for cat adoption using a design thinking method that focuses on user experience and is effective in solving complex problems, and the best solution has not yet been found. The results of a comparison of the current cat adoption business process simulation and recommendations decreased by 51.45% or 23.5 minutes, which means it is more effective and efficient. The final result of this research is a high-fidelity prototype solution design. The solution design was evaluated using usability testing and the User Experience Questionnaire for ten respondents. The results of the usability test obtained the value of the effectiveness aspect is 91.667%, the efficiency aspect is 0.1377 goals/second, and the satisfaction aspect is 88.75 or grade A(excellent) using the system usability scale. In UEQ, the results showed that the average value of the attractiveness scale is 2.77(excellent), the perspicuity scale is 2.50(excellent), the efficiency scale is 2.70(excellent), the dependability scale is 2.53(excellent), the stimulation scale is 2.75( excellent), and novelty scale is 2.40(excellent).